Susceptibility of White-Tailed Deer (Odocoileus virginianus) to SARS-CoV-2 - Palmer, Mitchell V.; Martins, Mathias; Falkenberg, Shollie; Buckley, Alexandra; Caserta, Leonardo C.; Mitchell, Patrick K.; Cassmann, Eric D.; Rollins, Alicia; Zylich, Nancy C.; Renshaw, Randall W.; Guarino, Cassandra; Wagner, Bettina; et al. (Journal of virology, 2021)
Given the presumed zoonotic origin of SARS-CoV-2, the human-animal-environment interface of the COVID-19 pandemic is an area of great scientific and public and animal health interest. Identification of animal species that are susceptible to infection by SARS-CoV-2 may help to elucidate the potential origin of the virus, identify potential reservoirs or intermediate hosts, and define the mechanisms underlying cross-species transmission to humans. The origin of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus causing the global coronavirus disease 2019 (COVID-19) pandemic, remains a mystery. Current evidence suggests a likely spillover into humans from an animal reservoir. Understanding the host range and identifying animal species that are susceptible to SARS-CoV-2 infection may help to elucidate the origin of the virus and the mechanisms underlying cross-species transmission to humans. Here, we demonstrated that white-tailed deer ( Odocoileus virginianus ), an animal species in which the angiotensin-converting enzyme 2 (ACE2)—the SARS-CoV-2 receptor—shares a high degree of similarity to that of humans, are highly susceptible to infection. Intranasal inoculation of deer fawns with SARS-CoV-2 resulted in established subclinical viral infection and shedding of infectious virus in nasal secretions. Notably, infected animals transmitted the virus to noninoculated contact deer. Viral RNA was detected in multiple tissues 21 days postinoculation (p.i.). All inoculated and indirect contact animals seroconverted and developed neutralizing antibodies as early as day 7 p.i. The work provides important insights into the animal host range of SARS-CoV-2 and identifies white-tailed deer as a wild animal species susceptible to the virus. IMPORTANCE Given the presumed zoonotic origin of SARS-CoV-2, the human-animal-environment interface of the COVID-19 pandemic is an area of great scientific and public and animal health interest. Identification of animal species that are susceptible to infection by SARS-CoV-2 may help to elucidate the potential origin of the virus, identify potential reservoirs or intermediate hosts, and define the mechanisms underlying cross-species transmission to humans. Additionally, it may also provide information and help to prevent potential reverse zoonosis that could lead to the establishment of new wildlife hosts. Our data shows that upon intranasal inoculation, white-tailed deer became subclinically infected and shed infectious SARS-CoV-2 in nasal secretions and feces. Importantly, indirect contact animals were infected and shed infectious virus, indicating efficient SARS-CoV-2 transmission from inoculated animals. These findings support the inclusion of wild cervid species in investigations conducted to assess potential reservoirs or sources of SARS-CoV-2 infection.